Paramoeba atlantica as a Natural Intracellular Niche for Vibrios in Marine Ecosystems - Onillon, Laura; Dufau, Anaïs; Delafont, Vincent; Amraoui, Hajar; Robino, Etienne; Perret, Angélique; Romatif, Océane; Pouzadoux, Juliette; Soldati, Thierry; Travers, Marie‐Agnès; Charrière, Guillaume M. (Environmental microbiology, 2025)
ABSTRACT Vibrios are a group of aquatic bacteria that include diverse pathogens for humans and marine animals. In their natural environment, these bacteria are subject to predation by heterotrophic protozoa, including free‐living amoebae. Previous studies suggested that some amoebae species can promote the environmental persistence and dissemination of pathogenic vibrios. However, most research has focused on model amoebae derived from freshwater habitats despite the prevalence and diversity of amoebae and vibrios in marine ecosystems. This study identifies a natural association between the marine amoeba Paramoeba atlantica and Vibrio bathopelagicus, a member of the Splendidus clade. Investigations at the cellular level revealed that V. bathopelagicus can resist digestion by P. atlantica and can swim and replicate in large digestive vacuoles for hours before being released by exocytosis. Furthermore, V. bathopelagicus exhibits virulence potential against oysters. Intravacuolar survival in P. atlantica was observed for various vibrios, and screening of clonally isolated free‐living marine amoebae revealed that many Paramoebidae are found associated with vibrios. Our findings show that Paramoebidae can act as a widespread intracellular reservoir for diverse vibrios. This provides new insights into the environmental intracellular niches and opportunistic strategies of vibrios in marine ecosystems. Various vibrios can colonise a large vacuole called VCV (Vibrio‐containing‐vacuole) within Paramoeba atlantica. The VCVs acidify and the vibrios multiply and remain alive inside the VCVs for hours. The vibrio found associated with Paramoeba atlantica can be pathogenic to oysters, suggesting that Paramoebidae are a potential reservoir for pathogens.